2015
DOI: 10.1177/1934578x1501000647
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Other Phenolic Compounds in Needles ofPinus peuceand Other Pine Species from the Macedonian Flora

Abstract: Flavonoids and other phenolic compounds in young needles of four pine species, Pinus peuce, P. nigra, P. mugo and P. sylvestris from the Macedonian flora were investigated. The amount of total phenols and total flavonoids were determined using Folin-Ciocalteau and aluminum chloride assay, respectively. The obtained results revealed that the total phenolic content (TPC) and total flavonoids content (TFC) varied among different pine species ranging from 9.8 to 14.0 mg GAE/g and from 3.3 to 7.2 mg CE/g of dried p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
2
20
2
Order By: Relevance
“…Comparatively, 2 showed a positive Cotton effect at 224 nm (Δ ε + 1.25), which was assigned the absolute configurations as 7′ S and 8′ R [ 25 ]. Compound 3 exhibited pseudomolecular signals with m / z 739 and fragment ions at m / z 593, 485, and 285 in its MS and MS/MS analytical spectra and tentatively identified as kaempferol coumaroyl-glucose-rhamnoside [ 24 ]. Its chemical structure was confirmed as kaempferol 3- O -α-(6‴- p -coumaroylglucosyl-β-1,4-rhamnoside) by comparison of its physical and spectral data with those reported [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, 2 showed a positive Cotton effect at 224 nm (Δ ε + 1.25), which was assigned the absolute configurations as 7′ S and 8′ R [ 25 ]. Compound 3 exhibited pseudomolecular signals with m / z 739 and fragment ions at m / z 593, 485, and 285 in its MS and MS/MS analytical spectra and tentatively identified as kaempferol coumaroyl-glucose-rhamnoside [ 24 ]. Its chemical structure was confirmed as kaempferol 3- O -α-(6‴- p -coumaroylglucosyl-β-1,4-rhamnoside) by comparison of its physical and spectral data with those reported [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that higher concentrations of catechin and taxifolin are due to climatic stress conditions like less rainfall, higher temperatures and longer duration of sun exposure. However, taxifolin was not found in P. nigra, and P. sylvestris needle extracts harvested in Macedonian flora [37]. Quercetin has been identified in extracts obtained with the highest concentration of ethanol (i.e., 50% to 90% (v/v)) having concentration values of 8.5 to 10.9 mg/L.…”
Section: Phenolic and Flavonoid Contents Of Pbementioning
confidence: 89%
“…It indicates aromatic rings in conjugation with C=C/C=O [ 64 , 65 ]. In needles, coumaric acid, stilbenes and flavonoids are reported [ 66 69 ]. To assign specific bands to these different aromatics and track them selectively, a critical survey of reference spectra is necessary (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%